A newly-designed sandwich-structured graphene–Pt–graphene catalyst with improved electrocatalytic performance for fuel cells1. Issue 10 (14th March 2015) - Zhao, Lei; Wang, Zhen-Bo; Li, Jia-Long; Zhang, Jing-Jia; Sui, Xu-Lei; Zhang, Li-Mei
<x xml:space="preserve">Abstract</x> A novel sandwich-structured G–P–G catalyst prepared by a simple, facile synthesis method exhibits 1.27 times higher activity for methanol electro-oxidation than that of Pt/graphene and the stability is improved by 70% as compared with Pt/graphene.